Does Accounting Method Choice for Business Combination Influence IPO Valuation? - Nazmi, Mohamed Zin (2004)
There are numerous studies that examined the choice of accounting methods by IPO firms as a device to manage earnings prior to going public (Aharony et al., 1993; Friedlan. 1994; Neill et al., 1995; Black et al., 2002). This study extends Neill et al. (1995) by examining the association between accounting method choice and IPO valuation in Malaysia. However, instead of using accounting policies that are related to depreciation and inventory, this study looks at accounting method for business combination namely the purchase vs. merger method. By examining 62 IPOs during 2001 and 2002, the multivariate analysis shows that, consistent with the hypotheses, the liberal accounting method for business combination is positively associated with offer price and negatively associated with first day closing price and underpricing. However. none of the coefficients associated with accounting method are statistically significant. IPO offer price is positively influenced by forecasted earnings, net tangible assets and firm size. First day closing price is significantly influenced by forecasted earnings. IPO consists of exclusively new shares issue (i.e. participation ratio by IPO entrepreneurs equals zero) yields higher underpricing, consistent with Habib and Ljungqvist (2001). As expected, another important determinant of IPO underpricing is over-subscription rate with highly oversubscribed IPO generates greater underpricing.